Theology Brewed in an African Pot (Hekima Review, 2008)
Theology Brewed in an African Pot is a theological text which responds to some fundamental questions raised by genuine African Christians. Its title suggests a way of doing theology from an African context. The author dedicates the study to two African mothers, a gender equality motif that cuts across his work. There are eleven chapters, preceded by an introduction and followed by a postscript.